Utilization Waste Material as Stabilizer on Kuantan Clayey Soil Stabilization - Achmad Fauzi, Abdul Wahab; Wan Mohd Nazmi, Wan Abdul Rahman; Zuraidah, Jauhari (2012)
The objective of this research is investigated the utilization of High Density Polyethylene (HDPE) and Glass as material stabilizer in Kuantan clayey soil stabilization. The research conducts soil engineering properties and strength test for various contents of HDP E and glass to different types of clayey soil from various sites in Kelantan. The Standard Compaction and California Bearing Ratio (CBR) were applied in soil samples to estimate the optimum mixture design. The samples were set up by mixing soil samples with various content of stabilizer at optimum water content. The variation content of stabilizer was 4%, 8% and 12% by dry total weight. The accomplishment of subgrade stabilization depends on the engineering properties of clay and characteristic of stabilizer [5, 6, 7, 8, 9, and 10]. The laboratory test result were shown the engineering properties of Kuantan Clayey soil and CBR were improved by adding Cutting HDPE and Crushed Glass as stabilizer.